Response of coastal phytoplankton pigment composition to tropical cyclone Fani. (December 2021) - Baliarsingh, Sanjiba Kumar; Lotliker, Aneesh Anandrao; Srichandan, Suchismita; Parida, Chandanlal; Roy, Rajdeep; Naik, R. Chandrasekhar; Nair, T.M. Balakrishnan; Barik, Kamal Kumar
Abstract: Phytoplankton pigment composition was evaluated during the pre-cyclone phase (PRCP) and post-cyclone phase (POCP) of tropical cyclone Fani in the coastal waters of the northwestern Bay of Bengal. The chromatographic analysis revealed higher pigment diversity and an increase in individual pigment concentration during POCP. Chlorophyll– a (chl– a ) was the dominant pigment during PRCP and POCP, followed by fucoxanthin. However, chl– a and fucoxanthin concentrations increased 18- and 14-folds, respectively, during the POCP, signifying Bacillariophyta bloom. Complementing microscopy confirmed the dominance of the toxic Bacillariophyta species Pseudo-nitzschia pungens (reaching 5.47 × 10 4 cells l −1 ) during the POCP. The cyclone-induced nutrient recharge of the ambient medium could have promoted phytoplankton growth, causing the reappearance of diatom bloom during the later phase of the pre-southwest monsoon. Small-sized Prymnesiophyta and Cryptophyta were not detected microscopically; however, they were identified by chromatographic analysis through pigment markers during POCP. Highlights: Higher pigment diversity and upsurge in individual pigments aftermath of cyclone Fani. Multifold increment in chlorophyll– a and fucoxanthin levels after passage of Fani. Toxic Bacillariophyta species Pseudo-nitzschia pungens preponderance after passage of Fani. Significant effect of cyclone-induced nutrient upsurge in altering phytoplankton community composition. Chromatographic detection of Prymnesiophyta and Cryptophyta, although not revealed from microscopy.